Nyāyasāra of Bhāsarvajña : with the commentary Padabhañjikā of Vāsudeva Sūri - Narayanan, T. K. (New Bharatiya Book Corporation, 2019)
Study of the Nyāyasāra, aphoristic work on Hindu logic and epistemology by Bhāsarvajña, 10th century Kashmiri scholar; includes complete Sanskrit text with Padabhañjikā commentary of Vāsudevasūri.